The Complex Crystal Structure and Abundant Local Defects of Zeolite EMM‐17 Unraveled by Combined Electron Crystallography and Microscopy. Issue 45 (4th October 2021) - Liu, Xiaona; Liu, Lingmei; Pan, Tingting; Yan, Nana; Dong, Xinglong; Li, Yuanhao; Chen, Lu; Tian, Peng; Han, Yu; Guo, Peng; Liu, Zhongmin
Abstract: In this study, we successfully solve polymorphs A and B of zeolite EMM‐17, which can only crystallize in sub‐micrometer‐sized crystals while containing complex stacking disorders, from the three‐dimensional (3D) electron diffraction (ED) data. This is the first time that the atomic structure of this polymorph has been ab initio solved, and the result reveals a unique 10(12)×10(12)×11‐ring channel system. Moreover, we acquire the first atomic‐resolution images of EMM‐17 using integrated differential phase‐contrast scanning transmission electron microscopy. The images allow us to directly observe polymorphs B and C and discover a large number of local structural defects. Based on structural features unraveled from the reciprocal‐space 3D ED data and real‐space images, we propose a series of energetically feasible local structures in EMM‐17. We also demonstrate that the unique porous structure of EMM‐17 enables efficient kinetic separation of C6 alkane isomers. Abstract : The complex crystal structure of EMM‐17 polymorphs A and B containing a unique 10(12)×10(12)×11‐ring channel system were directly solved using continuous rotation electron diffraction data. Polymorph C and a large number of structural defects were observed at the atomic resolution by integrated differential phase‐contrast scanning transmission electron microscopy. EMM‐17 exhibits excellent kinetic separation ability for C6 alkane isomers.